A complementary approach for energy efficiency and comfort evaluation of renovated dwellings in Southern Europe. (October 2017) - Magalhães, Sílvia A.; de Freitas, Vasco P.
Abstract: The European Directive on Energy Performance of Buildings, 2010/31/EU (EPBD recast), provided the framework on which all member states should improve their buildings' 'energy efficiency'. However, the application of this Directive should account for the specific climate conditions, economic and cultural background, and the real heating/cooling habits of each country. The Energy Certificate is a label that quantifies the nominal energy consumption needed to achieve predefined comfort conditions, comprising a methodology that is fundamental for countries where there is a permanent demand for heating during the winter. Nevertheless, in Southern European Countries, due to specific climate, economy (low incomes and expensive energy costs) and culture (behavior and habits), a permanent heating practice does not exist. Therefore, it is essential to characterize Southern European Buildings in a complementary way. This study proposes a methodology to quantify a "Passive Discomfort Index" by calculating the temperatures outside the comfort range, within the building, in realistic use conditions, that is, free-floating temperature or intermittent heating. This approach is especially important for retrofitting interventions on existing dwellings, where traditional energy improvement measures, mainly insulation measures, are often highly intrusive. The comfort assessment for Portuguese climate and a 19 th century building was performed with an advanced numerical simulation tool, WUFI Plus, previously validated by experimental monitoring. Results suggest that insulation thickness has a very low impact on discomfort hours and energy consumption for intermittent heating scenarios. And, for free-floating scenarios, insulation measures may not have any significant impact at all. In addition, a logarithmic relationship seems to exist between heating scenarios and energy consumption/discomfort hours.